The dipeptide carnosine alleviates acute pancreatitis in an experimental model - Heresh Rezaei; Saeed Heidari; Mohammad Mehdi Ommati; Babak Taheri; Forouzan Khodaei; Mohammad Ali Dehghani; Ayeh Rowhanirad; Azadeh Veisi-Goshtasb; Zahra Honarpishefard; Negar Azarpira; Hossein Niknahad; Reza Heidari (Trends in Pharmaceutical Sciences)
Acute pancreatitis (AP) is a severe inflammatory disorder with a significant risk of mortality. However, restricted pharmacological treatments are available against this complication. Carnosine is an endogenous dipeptide with various pharmacological effects, including antioxidative and anti-inflammatory properties. The current study was designed to evaluate the impact of carnosine in an experimental model of AP. For this purpose, mice received arginine (two 4 g/kg doses, one-hour intervals, i.p) to induce AP. Then, animals received carnosine (50, 250, and 500 mg/kg, i.p). Serum levels of amylase, lipase, and glucose were significantly increased (P<0.001) in the current AP model. Moreover, alterations in oxidative stress biomarkers in the pancreas, including ROS formation, decreased antioxidant capacity, lipid peroxidation, and glutathione depletion, were detected in the AP group (P<0.001). A significant increase in the pancreatic level of pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) was also evident in the l-arginine-treated mice (P<0.001). The major pancreatic tissue histopathological changes in the current AP model were the infiltration of inflammatory cells to the pancreas tissue, fluid accumulation, and acinar cell vacuolization/necrosis (P<0.05). Carnosine significantly reduced serum biomarkers of pancreas injury, alleviated oxidative stress, decreased pro-inflammatory cytokine levels, and improved histopathological changes in the pancreas of mice with AP (P<0.001). These findings suggest that carnosine is a protective agent in pancreatitis, with its antioxidative and anti-inflammatory properties playing a pivotal role in its mechanisms of action. Further research is needed to confirm these protective effects in clinical studies and assess carnosine safety in AP.